1979
DOI: 10.1073/pnas.76.11.6009
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular dye-marked enkephalin neurons in the magnocellular preoptic nucleus of the goldfish hypothalamus.

Abstract: A method that combines intracellular recording, dye marking, and immunocytochemistry makes the study of functional and morphological aspects of enkephalin neurons in the magnocellular preoptic nucleus of the goldfish hypothalamus feasible. By use of multiple techniques, enkephalin neurons can be distinguished from other brain cells and can be reconstructed from drawings of serial sections containing the dye-injected opioid cells. These enkephalin cells and their processes measure 14-42,um provided important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Its popularity is due to its intense fluorescence, stability during illumination, and compatibility with a variety of embedding procedures. As a result, LY is now used in a variety of biological systems (Buhl and Dann, 1988;Buhl and Lubke, 1989;Buhl and Schlote, 1987;Buhl et al, , 1990Einstein, 1988;Katz, 1987;Lubke and Albus, 1989;Reaves and Hayward, 1979;Rho and Swanson, 1987;Smithson et al, 1983;Masland, 1984, 1985;Wouterlood et al, 1990; see also Djamgoz and Kolb, this issue; Meredith and Wouterlood, this issue). After the introduction in fixed tissue (LY injection into retinal ganglion cells; Tauchi and Masland, 19841, this technique in area 17 of a 5-day-old kitten.…”
Section: Photoconversion Of Ly-filled Neurons In Fixedmentioning
confidence: 99%
See 1 more Smart Citation
“…Its popularity is due to its intense fluorescence, stability during illumination, and compatibility with a variety of embedding procedures. As a result, LY is now used in a variety of biological systems (Buhl and Dann, 1988;Buhl and Lubke, 1989;Buhl and Schlote, 1987;Buhl et al, , 1990Einstein, 1988;Katz, 1987;Lubke and Albus, 1989;Reaves and Hayward, 1979;Rho and Swanson, 1987;Smithson et al, 1983;Masland, 1984, 1985;Wouterlood et al, 1990; see also Djamgoz and Kolb, this issue; Meredith and Wouterlood, this issue). After the introduction in fixed tissue (LY injection into retinal ganglion cells; Tauchi and Masland, 19841, this technique in area 17 of a 5-day-old kitten.…”
Section: Photoconversion Of Ly-filled Neurons In Fixedmentioning
confidence: 99%
“…In addition to older neuroanatomical methods such as the classical Golgi-impregnation technique, degeneration techniques, and other methods based on the transport of large macromolecliles, tracing with fluorescent dyes and intracellular injections with LY are relatively new techniques in neurobiology. The latter fluorescent dyes were introduced as alternative and additional neuroanatomical markers to study the connectivity and morphology of neurons in the CNS (Bentivoglio and Su, 1990;Buhl and Lubke, 1989;Einstein, 1988;Godeinent et al, 1987;Honig and Hume, 1989;Katz, 1987;Kuypers et al, 1977Kuypers et al, , 1979Lubke and Albus, 1989;Reaves and Hayward, 1979;Sandell and Masland, 1988;Smithson et al, 1983;Stewart, 1978Stewart, , 1981Tauchi and Masland, 1985;Wouterlood et al, 1990). Because DAB can now be photoconverted with a number of fluorescent markers into a stable reaction product, using a simple protocol originally described by Maranto (1982), the capability of these methods is now no longer restricted to the fluorescence microscope level.…”
Section: Concluding Remarks and Further Prospects Of The Photoconversmentioning
confidence: 99%
“…In experiments where Lucifer Yellow was not used the second antibody was that coupled to FITC. When cells had been filled with Lucifer Yellow, a second antibody coupled to rhodamine was used so that the immunofluorescence could be easily distinguished from that of Lucifer Yellow (Reaves & Hayward, 1979). The effect of the immunohistochemical procedures on the Lucifer Yellow fluorescence was monitored at each step and it was found that, although the intensity was reduced, well-filled cells and their processes remained readily identifiable.…”
Section: Procemsing For Immunohidtochemi8trymentioning
confidence: 99%
“…After fixation the preparation was dehydrated and rehydrated before being exposed for at least 12 h to an anti-VIP antibody (code 7913 from Dr J. H. Walsh) raised in a rabbit; it was then washed and exposed for 1 h to a second (anti-rabbit) antibody coupled to rhodamine (Cappel Laboratories). Use of rhodamine allowed the immunofluorescence to be distinguished from the Lucifer Yellow fluorescence in the filled cells (Reaves & Hayward, 1979).…”
Section: Inhibition In Vip Neurones Methodsmentioning
confidence: 99%